Prevalence of bacteriocins and their co-association with virulence factors within Pseudomonas aeruginosa catheter isolates - Snopkova, Katerina; Dufkova, Kristyna; Klimesova, Petra; Vanerkova, Martina; Ruzicka, Filip; Hola, Veronika (International journal of medical microbiology, 2020)
Urinary tract infections represent common nosocomial infectious diseases. Bacteriocin production has been recently described as a putative virulence factor in these infections but studies focusing particularly on Pseudomonas aeruginosa are not available. Therefore, we assessed the prevalence of the bacteriocin genes, their co-occurrence and their co-association with previously detected virulence factors in a set of 135 P. aeruginosa strains from catheter-associated urinary tract infections (CAUTIs). The overall bacteriocinogeny reached 96.3 % with an average of 3.6 genes per strain. The most frequently detected determinants were the encoded pyocins S4 (76.3 %), R (69.6 %), and S2 (67.4 %). A statistically significant co-occurrence and a negative relationship were observed between several pyocin types. Particular pyocins exhibited associations with biofilm formation, production of pyochelin, pyocyanin, antibiotic-degrading enzymes, overall strain susceptibility and resistance, and motility of the strain. Co-occurrence of the pyocins S2 and S4 (p<<0.0001; Z = 13.15), both utilizating the ferripyoverdine receptor FpvAI, was found but no relation to pyoverdine production was detected. A negative association (p = 0.0047; Z=-2.83) was observed between pyochelin and pyocin S5 utilising the ferripyochelin receptor FptA. Pairwise assays resulted in 52.1 % inhibition which was equally distributed between soluble and particle types of antimicrobials. In conclusion, pyocin determinants appear to be important characteristics of CAUTI-related P. aeruginosa isolates and could contribute to their urovirulence.
Keywords: faktory virulence; Catheters; Bacteriocin; Prevalence; katétry; prevalence; Urinary Tract Infections; Humans; Pyocin; infekce močového ústrojí; lidé; CAUTI; Bacteriocins; Virulence Factors; Siderophores; bakteriociny; Pseudomonas aeruginosa